Sistem Pendukung Keputusan Berbasis Web untuk Pemilihan Lokasi Strategis Coffee Shop di Kota Yogyakarta dengan SMART - Siswirawan, Andhika Prasetyo; Fansyuri, Maulana (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2025)
The coffee shop industry in Yogyakarta has grown rapidly along with the increasing coffee consumption and the city’s strong tourism appeal. Selecting a strategic location is a key success factor for coffee shop businesses; however, this process is complex as it involves multiple criteria such as population density, crowd level, accessibility, rental price, and competition. This study aims to develop a web-based Decision Support System (DSS) using the Simple Multi-Attribute Rating Technique (SMART) method to assist entrepreneurs in determining the optimal coffee shop location. The research applied a quantitative approach through several stages: literature review, criteria identification, data collection, system design with UML, implementation using PHP-MySQL, and testing through Black Box and White Box. The results show that the developed system can provide objective, measurable, and user-friendly location recommendations. System testing confirmed that all functions work as designed, while user feedback indicated a high level of satisfaction. In conclusion, the web-based DSS application using the SMART method is effective for selecting strategic coffee shop locations in Yogyakarta. This system provides a practical solution for entrepreneurs to enhance decision-making quality, reduce subjectivity, and support business success in an increasingly competitive market.